(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Bacteriophages, or phages, are virus-like agents that infect bacteria. Lytic phages can be used as biological antimicrobials and can kill bacteria. Objective:To formulate therapeutic phage cocktails able to overcome multiple-drug resistant Escherichia coli in Iraq. Methods: Escherichia coli were isolated from Iraqi hospitals and were characterized in terms of site of isolation, patient’s age, sex, and disease. Antibiotics sensitivity test was used to evaluate antibiotics effectiveness. Accordingly, isolated bacteria were grouped in terms of resistance to antibiotics, infection type, and infection site. Wild phages specific to Escherichia coli were isolated from different areas. The isolated phages were optimized and their biokinetics were measured. Results: A total of 10 samples of Escherichia coli, 7 samples of them revealed specific phages. The formulated phage cocktail to Escherichia coli was shown to remarkably minimize the bacterial resistance to individual phages. Conclusion: Bacteriophage cocktails are useful to tackle the problem of MDR bacteria. Keywords:Multi-drug resistance, bacteriophage, phage therapy, Escherichia coli.